Windscale 1957 - Arnold, Lorna. author. aut Link
XXV, 235 p.
Keywords: The aim of this book is to set the 1957 Windscale accident in its historical context in the immediate post-war period and the early days of the Cold War, to describe the event and its consequences and to evaluate it from the vantage point of 1990.